FranchiseGlobal.com Business Development Strategy: Analysis Using Financial Planning at FranchiseGlobal.com - Irvan Rizki Septian; Edi Hamdi; Rhian Indradewa; Ferryal Abadi (Publikasi Indonesia, 2024)
This research aims to analyze the business development strategy of FranchiseGlobal.com through a comprehensive financial planning approach. As a digital platform offering franchise and business opportunities, FranchiseGlobal.com aspires to become the leading and innovative online franchise media. The research analyzes short-, medium-, and long-term financial planning to achieve profitability and business sustainability. A qualitative descriptive method and thematic analysis were employed for data analysis. The study examines key financial planning elements, including revenue planning, cost management, capital requirements, and five-year financial projections. The results show that sound financial planning can help the company achieve profitability targets within five years, indicated by a positive NPV, IRR above 10%, and a payback period of less than four years. The company's projected revenue growth is expected to remain stable through diversification of revenue streams and efficient capital management. The study concludes that appropriate financial strategies will be a crucial foundation for FranchiseGlobal.com to become Indonesia's leading digital franchise platform.